Alternative Payment Models and Academy Advocacy. (23rd August 2013) - Setzen, Michael; Denneny, James C.; Waguespack, Richard W.; Koopmann, Charles F.; Lorenz, Robert R.; Boss, Emily F.; Lafreniere, Denis C.
Abstract : Program Description: The physician payment landscape is changing as quality measures become more intertwined with payment. This miniseminar outlines the efforts of the Physician Payment Policy Work Group (3P) to prepare members for the implementation of the Affordable Care Act by giving them the tools to participate in diverse payment systems. Topics include public and private payment models including accountable care organizations (ACOs), bundling, and the importance of measures in the future of quality and payment initiatives. Presenters will discuss strategies including how resources such as Clinical Indicators and Policy Statements are used to advocate for appropriate policies by health insurance companies for coverage of services. Educational Objectives: 1) Comprehend future healthcare reform initiatives, new payment models, and Academy efforts to prepare members for changes to how they will receive payment for services. 2) Recognize the measure sets we have formally developed in otolaryngology (sinusitis, otitis externa/otitis media) and how many providers can and will apply these measures to practice. 3) Be aware of Academy strategies for interaction with public and private payers and effective membership involvement.